Peningkatan keterampilan penalaran matematis melalui pendekatan realistic mathematics education (RME) pada peserta didik kelas V SD - Halimah Halimah (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2020)
This research aims at improving mathematical reasoning skills through the implementation of Realistic Mathematics Education approach. This is a two-cycles Classroom Action Research (CAR). Each cycle consists of three meetings. There are four stages in every meeting that are planning, acting, observing, and reflecting. The subject of this research is 30 students of the fifth grade of SD Negeri Tunggulsari 1 Surakarta, academic year 2019/2020. Observation, interview, tests, and documentation are used as the data collection technique. Triangulation is used to check the validity of this research. The data are analyzed using Miles- Huberman interactive analysis model. The first cycle began with the first learning resulting in increased 47% with 72,00 of average, second learning was increased 3% with 74,00 of average and the third of learning was increased 10% with 74,00 of average. This research continued with second cycle with percentage of students' classical mastery 73% with 82,00 of average in first learning, second learning has percentage of students' classical mastery 77% with 82,00 of  average and the last learning has percentage of students' classical mastery 83% with 87,00 of average. Those results indicate that the mathematical reasoning skill of the fifth grade students of SD Negeri Tunggulsari 1 Surakarta academic year 2019/2020 can be improved by the implementation of Realistic Mathematics Education approach.